A study of the apprenticeship course of the Bachelor of science in Interior Design program - Ramos, Carines Angeline Ramos; Faustino, Johanna Acab. (Quezon City University of the Philippines Diliman, 2007)
The research focused its study on the Apprenticeship course of the Bachelor of Science in Interior Design of the University of the Philippines, Diliman Quezon City. It sought to determine if the on-the-job training and other course requirements address the objectives from the 1993-1994 course syllabus. Objectives of this research included identifying and enumerating the actual and relevant tasks done in the on-the-job training and an assessment of the work related factors that affected the students' apprenticeships in the different design industries. Information gathered from this study would help build a strong foundation for the course and aid in the assessment of the Interior Design 178 curriculum. Systematic sampling was used wherein interior design students from batches 2006 and 2007 were chosen to be the respondents in the study. Thirty five of the sixty four possible respondents gave their views by answering the sent or given questionnaire. Results showed each task categorized according to its relationship with the objectives of the course from the 1993-1994 course syllabus. Tasks in the different apprenticeships were listed according to its frequency in the different design industries. Results inferred that apprentices preferred design related tasks and tend to neglect and disapprove of the basic office work or non-design related tasks. A total of 34.3 percent of the respondents were concerned with the given time allotted for each apprenticeship. Apprentices wanted more time and attention to these on-the-job trainings. The minor and major projects were the second concern of the apprentices, most believed it was essential while some thought otherwise. On the other hand, 8.5 percent suggested that there should be assistance in aiding students to find design companies.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Curricula -- University of the Philippines (Diliman).